Ogoljavanje identiteta stranca: Udio povijesti, između reformacije i tranzicije, u Jančarevu romanu Galijot - Latković, Ivana; Kovač, Zvonko (Slavia Centralis, 2020)
Denudation of Identity of a Foreigner : The Share of History between the Reformation and the Transition in Jančar's Novel Galjot . In a wide spectrum of created forms of historical genre, Jančar’s novel Galijot, with its theme of the character of a foreigner, sets this issue as a semantic and conceptual knot of his novel and thus represents an optimal point in his interpretative – analytical act.
Keywords: Historical novel; D. Jančar; Galjot; character of foreigner; attainment/denudation of identity